PERANAN PONDOK PESANTREN DALAM PENGEMBANGAN KULTUR ISLAM NUSANTARA - Ikbal, Muhammad (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
So far, Indonesian society has been known as a multicultural society, because it prioritizes culture. If there is mention of Islam Nusantara in Indonesia, of course it will be related to the term plurality. Islam Nusantara itself recognizes that culture is part of religion. So, why was Islam easily accepted by Javanese people at that time, because they prioritized culture without reducing the purity of Islamic teachings themselves. This research includes field research, a qualitative research method with a case study type of research and is descriptive in nature. Islam in the Archipelago and Islam Nusantara are similar sentences but in their meaning they have different meanings. In terms of terminology, the sentence Islam in the Archipelago has the meaning of the Islamic religion which is developing and has become one of the recognized religions in the archipelago, while Islam Nusantara at least has the meaning of the Islamic religion which has interaction, contextualization, universal Islam with all social, cultural and religious realities in Indonesia in particular, and/or Islam that is unique to the archipelago. Islamic boarding schools play a very important role in maintaining, preserving and developing the Islamic culture of the archipelago. Islamic boarding schools are able to form character and personality that is in accordance with the Islamic values ​​of the archipelago, such as tolerance, diversity and harmony both within religions and between religious communities. Nusantara Islam is a unique Indonesian style of Islam, namely a combination of Islamic theological values ​​with local traditional values, culture and customs in the country. The character of Indonesian Islam shows that there is local wisdom in the archipelago that does not violate Islamic teachings.